The relationship among innovative output, productivity, and profitability: a test comparing USPTO and EPO data - Enrico Santarelli; Francesca Lotti (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The aim of this paper is to test whether patent-based indicators are still reliable measures of innovativeness in light of organizational changes in the field of Intellectual Property Rights (IPR) protection and the regulatory reforms already under way respectively at the U.S. Patent and Trademark Office (USPTO) and the European Patent Office (EPO). For most high-tech industries, patents represent an outcome of the production process and their number can be taken as a proxy for a firms ability to improve its productivity growth and profitability. The case study reported here concerns the biotechnology industry in Italy, whose firms, by definition, have Intellectual Property (IP) activities in their portfolios. For this purpose, we use a unique data set which collects balance sheet items and patent information from EPO and USPTO. After linking firms financial and production data with the patent information, we estimate a modified knowledge production function in which the dependent variable is alternatively (labor) productivity growth and profitability. Our findings show that only patents with the EPO, along with larger firm size, have a statistically significant relationship with productivity growth and profitability. This suggests that firms pursue different strategies when patenting with the USPTO and the EPO, and that this difference reflects statutory changes made to the former during the relevant period.
Keywords: L25; L65; O34; 330; IP Protection; Productivity; Profitability; Biotechnology Industry; Italy; Innovation; Patent; Arbeitsproduktivität; Rentabilität; Biotechnische Industrie; Italien; Patentrecht; Reform; EU-Staaten; USA